Mental health disparities between hispanic and non‐hispanic parents of childhood cancer survivors. Issue 9 (19th March 2013) - Meeske, Kathleen A.; Sherman‐Bien, Sandra; Hamilton, Ann S.; Olson, Anamara Ritt; Slaughter, Rhona; Kuperberg, Aura; Milam, Joel
Abstract Background Parents of childhood cancer survivors (CCS) experience considerable distress related to their child's cancer. However, little is known about cultural variation in this experience. We examine parental distress, specifically symptoms of post‐traumatic stress (PTSS) and depression, comparing Hispanic and non‐Hispanic parents of CCS. Procedure Seventy‐nine Hispanic and 60 non‐Hispanic parents of CCS (currently aged 14–25, off treatment ≥2 years) completed questionnaires assessing demographics, depression, PTSS, perceived stress, and child's health status/quality of life (QOL). t‐Tests and chi‐square statistics were used to compare differences in demographic characteristics between Hispanic and non‐Hispanic parents and multivariable regression was used to determine independent risk factors associated with parental PTSS and depression. Results Hispanic parents were significantly younger, had less education, lower incomes and reported significantly more PTSS and depressive symptoms than non‐Hispanic parents (all P‐values < 0.0001). Among Hispanic parents, foreign birthplace predicted higher PTSS after controlling for other factors (P < 0.001). Hispanic parents, regardless of birthplace, reported more depressive symptoms than non‐Hispanic parents (US‐born, P < 0.05; foreign‐born, P < 0.01). For PTSS and depression, there were positive relationships with parental stress and negative relationships with the child's psychosocial QOL. Hispanic and non‐Hispanic CCS did not differ significantly on disease and treatment factors or health‐related QOL. Conclusions Hispanic parents of CCS may be at greater risk for poorer mental health outcomes. Ethnic‐specific factors (e.g., acculturation, immigration status, and previous trauma) may influence parents' responses and adjustment to their child's cancer. Research is needed to determine how to meet the needs of the most vulnerable parents. Pediatr Blood Cancer 2013;160:1470–1477. © 2013 Wiley Periodicals, Inc.